2000
DOI: 10.1177/074193250002100102
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Social Attainments of Children with Mental Retardation in General Education and Special Education Settings

Abstract: Parents, professionals, and researchers have been concerned about the most appropriate placement for children with mental retardation. To shed light on the efficacy of integration, 36 studies were reviewed on the academic and social attainments of school-age children with mental retardation. Results show that children in general education classes do not attain social acceptance ratings at as high a level as do their typically developing peers. When comparing children with mental retardation in general educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
17

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(157 citation statements)
references
References 60 publications
8
132
0
17
Order By: Relevance
“…Of nine studies undertaken prior to 2000, Freeman and Alkin (2000) found no significant difference between the academic achievement of students with ID educated with segregated and inclusive classrooms. The authors did observe, however, that the greater the amount of time spent in an inclusive classroom, the more positive the results.…”
Section: Academic Outcomesmentioning
confidence: 87%
See 1 more Smart Citation
“…Of nine studies undertaken prior to 2000, Freeman and Alkin (2000) found no significant difference between the academic achievement of students with ID educated with segregated and inclusive classrooms. The authors did observe, however, that the greater the amount of time spent in an inclusive classroom, the more positive the results.…”
Section: Academic Outcomesmentioning
confidence: 87%
“…Although the impact of IE on the academic achievement of children with mild disabilities has been thoroughly investigated, this is not the case for children with intellectual disabilities (ID), especially those with more substantial support needs (Bouck, 2007;Freeman & Alkin, 2000;Hunt & McDonnell, 2009). Of nine studies undertaken prior to 2000, Freeman and Alkin (2000) found no significant difference between the academic achievement of students with ID educated with segregated and inclusive classrooms.…”
Section: Academic Outcomesmentioning
confidence: 99%
“…Cette option politique et la loi qui la sous-tend 1 reconnaissent comme un droit de l'enfant ayant des besoins particuliers d'être scolarisé dans l'école de sa communauté de domicile. Avec cette réforme, c'est la capacité de l'école à intégrer ces élèves (Bless et Kronig, 1999) qui est interrogée, et non l'efficacité de l'inclusion scolaire (Fisher et Meyer, 2002;Freeman et Alkin, 2000;Hardman et Dawson, 2008;Mitchell, 2008;Saint-Laurent et al, 1998).…”
Section: Contexteunclassified
“…The reduction of full-time special education in Norway has its basis on humanistic ideas and research on academic results in segregated and inclusive environments (Markussen et al 2007). Several studies show that the academic results seem to be better in inclusive environment in comparison to segregated environment (Freeman and Alkin 2000;Myklebust 2006;Stangvik 1970), and children with special needs who have attended normal classes have easier access to further studies (Markussen 2004). The Norwegian school, therefore, regards the link between academic standards and social acceptance as very critical.…”
Section: The Right To Learn and Special Educationmentioning
confidence: 99%